In Vivo and In Vitro Antidiabetic Activity of Terminalia paniculata Bark: An Evaluation of Possible Phytoconstituents and Mechanisms for Blood Glucose Control in Diabetes. (14th July 2013) - Ramachandran, Subramaniam; Rajasekaran, Aiyalu; Adhirajan, Natarajan
Abstract : The present study was aimed to investigate in vivo, in vitro antidiabetic activity of aqueous extract of Terminalia paniculata bark (AETPB) and characterize its possible phytoconstituents responsible for the actions. Type 2 diabetes was induced in rats by streptozotocin-nicotinamide (65 mg/kg–110 mg/kg; i.p. ) administration. Oral treatment of AETPB using rat oral needle at 100 and 200 mg/kg doses significantly (P < 0.001 ) decreased blood glucose and glycosylated haemoglobin levels in diabetic rats than diabetic control rats. AETPB-treated diabetic rats body weight, total protein, insulin, and haemoglobin levels were increased significantly (P < 0.001 ) than diabetic control rats. A significant (P < 0.001 ) reduction of total cholesterol and triglycerides and increase in high-density lipoprotein levels were observed in type 2 diabetic rats after AETPB administration. Presence of biomarkers gallic acid, ellagic acid, catechin, and epicatechin in AETPB was confirmed in HPLC analysis. AETPB and gallic acid showed significant (P < 0.001 ) enhancement of glucose uptake action in presence of insulin in muscle cells than vehicle control. Also AETPB inhibited pancreatic α -amylase and α -glucosidase enzymes. In conclusion, the above actions might be responsible for the antidiabetic activity of AETPB due to presence of gallic acid and other biomarkers.